2020
DOI: 10.13057/biodiv/d210353
|View full text |Cite
|
Sign up to set email alerts
|

Local indigenous strategy to rehabilitate and conserve mangrove ecosystem in the southeastern Gulf of Kupang, East Nusa Tenggara, Indonesia

Abstract: Abstract. Sadono R, Soeprijadi D, Susanti A, Matatula J, Pujiono E, Idris F, Wirabuana PYAP. 2020. Local indigenous strategy to rehabilitate and conserve mangrove ecosystem in the southeastern Gulf of Kupang, East Nusa Tenggara, Indonesia. Biodiversitas 21: 1250-1257.  The existence of local communities around mangrove ecosystems plays essential role to support the effort of conservation programs in this area. This study is aimed to investigate a set of situation faced by local communities in the southeastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…A. marina and S. alba become the most dominant species in this ecosystem since the availability of plant materials of both species were relatively high and easy to find for using in reforestation programs. Our statement was also supported by the previous study reported by Sadono et al (2020) which described the history of mangrove reforestation in Tanah Merah.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…A. marina and S. alba become the most dominant species in this ecosystem since the availability of plant materials of both species were relatively high and easy to find for using in reforestation programs. Our statement was also supported by the previous study reported by Sadono et al (2020) which described the history of mangrove reforestation in Tanah Merah.…”
Section: Resultssupporting
confidence: 91%
“…However, this study observed that the variation of growth in this area was more influenced by the different age of stand. It was confirmed by the study from Sadono et al (2020) that documented the process of mangrove reforestation in Tanah Merah. According to the study, the planting period of mangroves in this area exceptionally varied due to influence of sea tide dynamics.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…For example, in Kenya, local tribes modestly harvest the timber, non-timber forest products and associated ecosystem goods provided by mangroves and surrounding systems to support their basic needs (Okello et al 2019). Similarly, in Indonesian communities, when people are aware and consider the sustainability of mangrove forests, they initiate mangrove rehabilitation efforts to ensure that the forests are a renewable natural resource (Rosaliza 2018, Sadono et al 2020. Mangrove protection efforts can be more impactful when national government and international organizations are involved.…”
Section: Population Density and Mangrove Soil Carbonmentioning
confidence: 99%